Penerapan Model Pembelajaran Discovery Learning Tipe Game Based Learning Berbantuan Platform Educaplay Untuk Meningkatkan Hasil Belajar Pendidikan Agama Hindu Dan Budi Pekerti Murid Kelas VII SMP Sapta Andika Denpasar - I Komang Hari Vahyu Werdhi Putra; Ni Made Anggreni; Ida Ayu Gde Wulandari (Yayasan Nanggroe Aceh Mulia, 2026)
This classroom action research aimed to improve students' learning outcomes in Hindu Religious Education and Character Education through the implementation of Discovery Learning with a Game Based Learning approach supported by the Educaplay platform. The study was conducted at SMP Sapta Andika Denpasar involving seventh-grade students in the academic year 2025/2026. The research employed the Kemmis and McTaggart classroom action research model consisting of planning, action, observation, and reflection stages conducted in two cycles. Data collection techniques included observation, documentation, and learning achievement tests. The results indicated that the implementation of Discovery Learning integrated with Game Based Learning and Educaplay created a more interactive and enjoyable learning atmosphere. Students became more active, motivated, and involved during the learning process. Consequently, students' learning outcomes improved from one cycle to the next. Therefore, the application of Discovery Learning with a Game Based Learning approach assisted by Educaplay can effectively improve learning outcomes in Hindu Religious Education and Character Education.